ОҚЫЎШЫЛАРДЫҢ МУЗЫКАЛЫҚ УҚЫПЛЫЛЫҒЫН РАЎАЖЛАНДЫРЫЎДЫН КОГНИТИВ ӨЗГЕШЕЛИКЛЕРИ - Пазылов, М.А. (FAN va JAMIYAT, 2023)
The article is about the importance of musical education in the development of student talents and the specific of the cognitive approach in the educational process.